Light-soaking effects and capacitance profiling in Cu(In, Ga)Se2 thin-film solar cells with chemical-bath-deposited ZnS buffer layers. Issue 48 (28th November 2016) - Yu, Hye-Jung; Lee, Woo-Jung; Wi, Jae-Hyung; Cho, Dae-Hyung; Han, Won Seok; Chung, Yong-Duck; Kim, Tae-Soo; Song, Jung-Hoon
Abstract : The relationship between interfacial defects and the electronic properties of CIGS solar cells with ZnS buffer layers was analyzed by C–V measurements with laser illumination. Abstract : We fabricated Cu(In, Ga)Se2 (CIGS) solar cells with chemical-bath deposited (CBD) ZnS buffer layers with different deposition times. The conversion efficiency and the fill factor of the CIGS solar cells reveal a strong dependence on the deposition time of CBD-ZnS films. In order to understand the detailed relationship between the heterojunction structure and the electronic properties of CIGS solar cells with different deposition times of CBD-ZnS films, capacitance–voltage ( C–V ) profiling measurements with additional laser illumination were performed. The light-soaking effects on CIGS solar cells with a CBD-ZnS buffer layer were investigated in detail using current density–voltage ( J – V ) and C – V measurements with several different lasers with different emission wavelengths. After light-soaking, the conversion efficiency changed significantly and the double diode feature in J – V curves disappeared. We explain that the major reason for the improvement of efficiency by light-soaking is due to the fact that negatively charged and highly defective vacancies in the CIGS absorber near the interface of CBD-ZnS/CIGS were formed and became neutral due to carriers generated by ultra-violet absorption in the buffer layer.